The contribution of the Hospital Energy First Aid to worker health (Research, Society and Development, 2020)
This research aims to evaluate the contribution of the Hospital Energy First Aid to the occupational health of professionals of a general hospital in Mossoró-RN, and to evaluate the presence of physical, psychological and social damages related to the work context. It is a mixed method research, a cross-sectional study and an action research. Quantitative data were collected through the Work-Related Damage Assessment Scale, qualitative data were obtained from a focus group and structured questionnaire. The research was carried out at Dr. Tarcísio de Vasconcelos Maia Regional Hospital, in the municipality of Mossoró-RN, whose target audience was the professionals of the institution, totaling 205 participants. The results showed significant work-related health damage, especially in the physical domain, especially musculoskeletal damage, followed by psychological and social domain. Survey participants report improvements in personal life and work environment after the implementation of the Hospital Energy First Aid. Integrative practices in the hospital work environment promote health to professionals, integral well-being, well-being and balance between mind, body and spirit.